Facies and Reservoir Characteristics of Cross-Bedded and Plane-Bedded Sandstone - Azri Hariz bin Abdul Raof, Azri (Universiti Teknologi Petronas, 2012)
Analysis of sedimentary and petrophysic properties for outcrops at Nyalau Formation were carried out to establish its geological and reservoir qualities. This was done with respect to the fact that most onshore geological formations nearby substantial hydrocarbon sources are studied for better delineation of the basin (Joanna M. Ajdukiewicz, 2010). Consequently cross-bedded structure has always represented a large fraction of sandstone reservoirs (M.E. Lord, 1989). At the geological site, various sedimentary properties are inferred individually for each beds. Such properties are then associated with facies model to define its depositional environment. Identification of these features requires skilled observations and measurements to be carried out at the outcrop; example includes dip-angle, lamina thickness, colour, mineralogy, and preliminary grain sorting. Besides these properties, sandstone distribution and lithology must also be recognized for bedforms fair sample size (D. Mikes, 2003). Moving on, samples are tested at lab facilities for sedimentary properties and petrophysic (Franz, 1985). Among the relevant test to be made are grain size / sorting test, porosity test (digital helium porosimeter), permeability test (multi-phase flow permeametry) Due to lack of time and resources, bed and boundary effects as well as heterogeneities effect are neglected, only focusing on the clean, most homogeneous sandstone sample available. The result for petrology was however inconclusive due to erroneous sample, allowing only facies model analysed linked with permeability qualities from mathematical correlation. Finally, the outcome was made in terms of reservoir qualities established as Good for both site studied. Conclusively the Samling outcrop offers a very good facies for sandstone reservoir formation due to clean HCS bed as well as wavy laminated sandstone. Its boundaries are often shale-mudstone or heterolithic which will become the no-flow trap. As for Kg Sg Plan, the outcrop has thicker clean sandstone layer. Another sandstone layer has mud clast heterogeneities thus will definitely hamper flow properties. It is therefore important to distinguish the heterogeneities and the continuity of the clean sandstone bed with respect to other potential no-flow zones.